A CRITIQUE TOWARDS MEN’S SUPERIORITY IN THE MYTH OF SISYPHUS - Rosyidy, Luqman (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2014)
This study is aimed to explain how men’s superiority is criticized in the culture of ancient Greece as reflected in the myth of Sisyphus. This is a descriptive qualitative study by using deconstruction of Derrida as the approaches. I collected the data from the myth of Sisyphus in The Greek Myths by Robert Graves, then I observed the binary oppositions appeared in the myth. Besides, I also considered on the culture of ancient Greece. Based on the theory provided, the data were analyzed one by one to find out the subversion of the ancent Greece culture as reflected in the myth of Sisyphus. This study finally found that the ancient Greece culture did not have concept about men’s superiority in their cultural system. Therefore, men who were claimed as the superior one to women did not have their superiority because the cultural system of ancient Greece did not have concept about men’s superiority.